2017
DOI: 10.1016/j.cgh.2016.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Infliximab and Adalimumab in Biologic-Naive Patients With Ulcerative Colitis: A Nationwide Danish Cohort Study

Abstract: Background & Aims We compared the effectiveness and safety of infliximab and adalimumab in biologic-naïve patients with ulcerative colitis (UC), in a nationwide register-based propensity score-matched study of patients in Denmark. Methods We collected data from 1719 adults with UC, 15–75 years old, in Denmark who were treated with either infliximab or adalimumab as their first biologic agent. We compared rates of all-cause hospitalization, UC-related hospitalization, major abdominal surgery, and serious infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
45
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 29 publications
5
45
2
1
Order By: Relevance
“…All‐cause and UC‐related hospitalisation rates were 38.1/100 PY and 21.4/100 PY, respectively. These rates are similar to those reported in a real‐life Danish study (all‐cause: 37.4/100 PY; UC‐related: 19.3/100 PY) . Combination therapy with a thiopurine, with or without previous exposure to thiopurines, was associated with better outcomes.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…All‐cause and UC‐related hospitalisation rates were 38.1/100 PY and 21.4/100 PY, respectively. These rates are similar to those reported in a real‐life Danish study (all‐cause: 37.4/100 PY; UC‐related: 19.3/100 PY) . Combination therapy with a thiopurine, with or without previous exposure to thiopurines, was associated with better outcomes.…”
Section: Discussionsupporting
confidence: 84%
“…The incidence of serious infection was lower in the CT-P13 group (HR 0.65; 95%CI: 0.48-0.88), but there was no significant difference in the incidence of solid or hematologic malignancies was observed between the two groups.All-cause and UC-related hospitalisation rates were 38.1/100 PY and 21.4/100 PY, respectively. These rates are similar to those reported in a real-life Danish study (all-cause: 37.4/100 PY; UCrelated: 19.3/100 PY) 33. Combination therapy with a thiopurine, with or without previous exposure to thiopurines, was associated with better outcomes.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…Our findings on comparative efficacy of first‐line pharmacotherapy in moderate‐severe ulcerative colitis builds on previous network meta‐analyses, and population‐based cohort studies which have suggested superiority of infliximab over adalimumab for inducing clinical response and decreasing the risk of hospitalisation . This may be related to difference in pharmacokinetics and bioavailability with different dosing schema (weight‐based vs fixed dose), adequacy of dose finding studies to fully explore dose response, and route of administration.…”
Section: Discussionmentioning
confidence: 99%